Case report: Mutations in DNAJC30 causing autosomal recessive Leber hereditary optic neuropathy are common amongst Eastern European individuals - Major, Toby Charles; Arany, Eszter Sara; Schon, Katherine; Simo, Magdolna; Karcagi, Veronika; van den Ameele, Jelle; Yu Wai Man, Patrick; Chinnery, Patrick F.; Olimpio, Catarina; Horvath, Rita (Frontiers in Neurology, 2023)
Background Leber Hereditary Optic Neuropathy (LHON) is the most common inherited mitochondrial disease characterized by bilateral, painless, subacute visual loss with a peak age of onset in the second to third decade. Historically, LHON was thought to be exclusively maternally inherited due to mutations in mitochondrial DNA (mtDNA); however, recent studies have identified an autosomal recessive form of LHON (arLHON) caused by point mutations in the nuclear gene, DNAJC30. Case Presentations In this study, we report the cases of three Eastern European individuals presenting with bilateral painless visual loss, one of whom was also exhibiting motor symptoms. After a several-year-long diagnostic journey, all three patients were found to carry the homozygous c.152A>G (p.Tyr51Cys) mutation in DNAJC30. This has been identified as the most common arLHON pathogenic variant and has been shown to exhibit a significant founder effect amongst Eastern European individuals. Conclusion This finding adds to the growing cohort of patients with arLHON and demonstrates the importance of DNAJC30 screening in patients with molecularly undiagnosed LHON, particularly in Eastern European individuals. It is of heightened translational significance as patients diagnosed with arLHON exhibit a better prognosis and response to therapeutic treatment with the co-enzyme Q10 analog idebenone.